2013
DOI: 10.2337/dc12-0505
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism Is Associated With Adipocyte Insulin Resistance and Plasma Adiponectin

Abstract: OBJECTIVEAdipocyte insulin resistance (IR) is a key feature early in the pathogenesis of type 2 diabetes mellitus (T2DM), and although scarce, data in the literature suggest a direct role for iron and iron metabolism–related factors in adipose tissue function and metabolism. Serum ferritin and transferrin were shown to be associated with muscle insulin resistance (IR) and T2DM, but little is known about the role of iron metabolism on adipose tissue. We therefore investigated whether markers of iron metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 40 publications
(65 reference statements)
7
75
3
1
Order By: Relevance
“…Contrary to our findings, a number of other studies have indicated a positive association between serum adiponectin and measures of human iron stores 9, 37, 38. These studies may be limited by the choice of surrogate for HIC.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, a number of other studies have indicated a positive association between serum adiponectin and measures of human iron stores 9, 37, 38. These studies may be limited by the choice of surrogate for HIC.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies may be limited by the choice of surrogate for HIC. In those three studies, inverse correlations were noted between serum ferritin and serum adiponectin; however, this only reached statistical significance in two of the studies 9, 37. These are interesting observations that were not seen in our cohort.…”
Section: Discussioncontrasting
confidence: 50%
“…The association of iron overload with increased risk of type 2 diabetes mellitus has been extensively demonstrated in recent systematic reviews and meta-analysis [5][6][7][8]. Circulating markers of iron overload are also positively associated with visceral and subcutaneous fat depots [9] and with adipocyte insulin resistance [10]. A previous study using the 3T3-L1 mouse cell line suggested the importance of iron-related genes in adipocyte physiology [11].…”
Section: Introductionmentioning
confidence: 92%
“…This finding is in accordance with the inverse association observed in the present study between the serum iron levels and the adiponectin levels independent of systemic inflammation in elderly women. However, two recent studies 30,31) demonstrated that adipocyte iron overload represses adiponectin transcription and the serum levels of adiponectin and that, consequently, the serum levels of ferritin and transferrin are inversely associated with those of adiponectin. Although we did not measure these variables, the latter finding is compatible with the current finding of an inverse association between the serum levels of iron and adiponectin.…”
Section: Discussionmentioning
confidence: 99%